2009
DOI: 10.1016/s1472-6483(10)60100-9
|View full text |Cite
|
Sign up to set email alerts
|

Circulating cell-free DNA as a potential biomarker for minimal and mild endometriosis

Abstract: It has recently been reported that high concentrations of circulating cell-free (ccf) nucleic acids in plasma and serum could be used as biomarkers for non-invasive monitoring a wide variety of malignant and benign proliferations and inflammatory conditions. Endometriosis is one of the most common benign gynaecological proliferations with inflammatory activation in premenopausal women. Real-time multiplex polymerase chain reaction was used for synchronized quantification of the glyceraldehyde-3-phosphate dehyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 21 publications
1
33
0
Order By: Relevance
“…Interleukin-6 with a cutoff point of 1.9 pg/mL gave a sensitivity of 71% and a specificity of 66% (3). Measuring the total amount of ccf nDNA provided a sensitivity of 70% and specificity of 87% (4). And a combination of CCR1mRNA, MCP1, and CA-125 measurements gave a sensitivity of 92.2% and specificity of 81.6% (5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interleukin-6 with a cutoff point of 1.9 pg/mL gave a sensitivity of 71% and a specificity of 66% (3). Measuring the total amount of ccf nDNA provided a sensitivity of 70% and specificity of 87% (4). And a combination of CCR1mRNA, MCP1, and CA-125 measurements gave a sensitivity of 92.2% and specificity of 81.6% (5).…”
Section: Discussionmentioning
confidence: 99%
“…Although blood tests looking at CA-125, cognate chemokine receptor 1 messenger RNA (CCR1 mRNA), interleukin-6, circulating cell-free nuclear DNA (nDNA), and a combination of CCR1 mRNA, monocyte chemotactic protein-1, and CA-125 have been proposed as diagnostic tests for endometriosis, none have had any success (1)(2)(3)(4)(5). At present, the so-called gold standard for diagnosis for endometriosis is an endoscopic surgical procedure, which involves a general anesthetic and hospital admission.…”
mentioning
confidence: 99%
“…They consume oxygen (O 2 ) and produce ATP by electron transport and oxidative phosphorylation taking place across the respiratory chain complexes located in the mitochondrial inner membrane. Mitochondrial alterations occur in several disorders, including malignant and benign proliferations and inflammatory conditions (15,59,26). The metabolic activity of the placenta is sustained throughout gestation by increasing mitochondrial activity and biogenesis (29).…”
mentioning
confidence: 99%
“…Several noninvasive tests for endometriosis have been proposed as follows: a combination of CCR1 mRNA, MCP1, and CA-125 measurements showed a sensitivity of 92.2% and a specificity of 81.6% [59]; IL-6 with a cutoff point of 1.9 pg/ ml showed 71% sensitivity and 66% specificity [60]; the total amount of ccf nuclear DNA provided 70% sensitivity and 87% specificity [18]; a serum anti-syntaxin 5 autoantibody showed 53.6% sensitivity and 72.2% accuracy [61]; a combined analysis of the mRNA levels of MMP-3, MMP-9, VEGF and survivin in the peripheral blood and the serum levels of CA-125 and CA19-9 in women with and without endometriosis showed 87% sensitivity [62]; serum IL-6 and peritoneal fluid TNF-a showed 90% sensitivity and 67% specificity and 90% specificity and 100% sensitivity, respectively [63]; the simultaneous evaluation of serum activin A and follistatin concentrations for the diagnosis of ovarian endometrioma showed 41% sensitivity and 90% specificity [64]; the sensitivity and specificity were 61% and 96% for a serum anti-TMOD3b-autoantibody, 78% and 93% for an antiTMOD3c-autoantibody and 78% and 96% for an antiTMOD3d-autoantibody (used in the detection of the early stages of endometriosis) [13]; the combined performance of IL-6, IL-8, TNF-a, hsCRP, CA-125, and CA19-9 diagnosed minimal to mild endometriosis with a sensitivity of 94% (specificity of 61%) during the secretory phase and with a sensitivity of 92% (specificity of 63%) during the menstrual phase [15]; and as a diagnostic marker, urinary vitamin Dbinding protein exhibited 58% sensitivity and 76% specificity [65].…”
Section: Caldesmon Is a Potential Marker For Endometriosismentioning
confidence: 99%
“…Many reports have suggested that various serum, peripheral blood, peritoneal fluid, urine, endometrial fluid, and biopsy markers are associated with endometriosis, such as tumor markers and polypeptides (CA-125, CA 19-9, SICAM-1), immunological markers (IL-6, TNF, antiendometrial antibodies and autoantibodies, and markers of oxidative stress), genetic markers (EGR-1, P450 aromatase, and PP14), circulating cell-free DNA, and tissue markers (P450 aromatase, cytokeratins, hormone receptors, PGP9.5-immunoactive nerve fibers) [7,[9][10][11][12][13][14][15][16][17][18][19]. The most commonly used serum marker for the clinical diagnosis of endometriosis, CA-125, is inadequate for the routine clinical assessment of endometriosis [20] because it has limited diagnostic accuracy in identifying early-stage endometriosis [21].…”
Section: Introductionmentioning
confidence: 99%